Community income analysis in lake Tempe Area, Wajo Regency. Issue 3 (July 2021) - Darma, R; Pada, A A T; Bakri, R; Darwis; Amrullah, A; Taufik, M
Abstract: In the Lake Tempe Area every rainy season is flooded. Where in the dry season the waters of Lake Tempe will experience drought and in the rainy season will experience overflowing water that causes flooding. Both seasons have an impact on the agricultural conditions of the community in the Lake Tempe Area. Due to the change of seasons is the dominant factor that causes local communities to adapt and interact with their environment which will also impact the income of people in the Lake Tempe Area. This study aims to analyze the income of people in the Lake Tempe Area Fishermen Farmers in farming activities, fishing and households, in Mallusesalo Village, Sabbangparu District, Wajo Regency and the results showed that during the period studied, namely from April to May 2019, the average household income of respondents in Mallusesalo Village in one year amounted to IDR 29, 034, 441 household income derived from agricultural and fishing income.